(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Demonetization in India has given a boost to digital payments and has encouraged people to go cashless. The government of India in tandem with RBI has been setting out plans to encourage electronic payments that enable India to move towards cashless economy, with the aim to curb the flow of black money and circulation of counterfeit currency. With the advent of technology, consumers have enormous options of making payments through debit cards, credit cards and internet banking, which facilitates the payment for the transactions more convenient and accessible. With the increased penetration of smart phones usage amongst Indians, mobile payments is gaining grounds in India. Besides being used to access internet, people use smart phones to store receipts, business cards and bills. But of late smart phones function as leather wallets, commonly known as “mobile wallet” or M-Wallet. M-Wallet services help the smart phones users to transfer money from bank to m-wallet and use that money to pay for services such as shopping, tickets, recharging and bill payments. M-Wallet not only offers convenience and security but also offers affordability over other modes of payment especially when transferring of money is involved. India is witnessing growth of M-wallet service providers like Paytm, Mobikwik, Vodafone m-pesa and others. The purpose of this study is to analyze and find out the status of adoption of M-wallet services and to find out the gender and age based variance in adoption of M-wallet modes of cashless payments/ transactions. The findings of this study suggest that adoption of M-wallet has increased due to three main factors convenience, ease of use, compulsion after demonetization. It has been found that there is gender and age based variance in the adoption of M-wallet.